2016
DOI: 10.4269/ajtmh.15-0710
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Genotype-Specific Immune Responses to Plasmodium falciparum Merozoite Surface Protein 1 in Kenyan Children from Regions of Different Malaria Transmission Intensity

Abstract: Abstract. Naturally acquired immunity to Plasmodium falciparum presents a changing landscape as malaria control programs and vaccine initiatives are implemented. Determining which immunologic indicators remain surrogates of past infection, as opposed to mediators of protection, led us to compare stability of immune responses across regions with divergent malaria transmission intensities. A repeat cross-sectional study of Kenyan children from a malariaholoendemic area and an epidemic-prone area was used to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…However, one study also found evidence that even in a region with high malaria infection, the levels of antibody can remain low [27]. Moreover, inherited immunity in the form of cellular responses (as measured by interferon gamma responses to MSP1) in infants living in a low transmission decline rapidly without the presence of malaria infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, one study also found evidence that even in a region with high malaria infection, the levels of antibody can remain low [27]. Moreover, inherited immunity in the form of cellular responses (as measured by interferon gamma responses to MSP1) in infants living in a low transmission decline rapidly without the presence of malaria infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 MSP1 elicits a humoral immune response in natural infections and somebut not allstudies have found a correlation between MSP1 antibody titers and protection from clinical malaria. [26][27][28][29][30] Antibodies against MSP1 can induce multiple effector mechanisms to control blood stage parasitemia, including directly blocking invasion of erythrocytes by merozoites and/or intraerythrocytic development, 23,[31][32][33][34] activation of complement, 35 and opsonization for monocyte-mediated phagocytosis and neutrophil granulocytemediated release of reactive oxygen species (ROS). 36,37 MSP1 can further elicit CD8 + T-cell-mediated cellular immune responses against liver stage parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies examining NK cells from children who experience severe disease would be useful to determine if the IL-10-producing NK cell population is lacking in these susceptible individuals. Likewise, samples from individuals that experience high or low Plasmodium exposure would further strengthen the assertion that NK cells playing a regulatory role through production of IL-10 develop following repeated Plasmodium exposure[55]. Previous studies have shown that CD4+ T cells from individuals in malaria endemic areas also display a marked increase in IL-10, which was dependent on malaria infection experience[30].…”
Section: Discussionmentioning
confidence: 91%